Formula dan Ekspresi Formulaik sebagai Aspek Pembangun Tema melalui Gaya Bahasa dalam Syair Melayu Riau Sultan Abdul Muluk: Analisis Sastra Lisan - Pratiwi, Dyani Prades; Komariya, Siti; Hawa, Andina Meutia (Puitika, 2024)
Syair is an old poem in the form of a song that has been passed down from generation to generation. As a form of oral literature, Syair is formed by the presence of formulas and formulaic that build the story in the poem. This study aims to find formulas and formulaic that build the theme of Syair Sultan Abdul Muluk from the province of Riau, Indonesia. The method used in this research is descriptive qualitative method and formula theory proposed by Albert B. Lord. The results showed that there were formulas and formulaic expression in the form of character names, place names, scenes, and times. However, in the time section it is found that time is described in a non-specific manner. This is due to differences in culture or character of the place and its people. The formulas and formulaic expression build the theme of the story, which is leadership. In addition, the results of the study also show that the style of language used as a storyteller is the language style commonly used in old poem, which is rhyming and containing metaphorical figures of speech.